1987
DOI: 10.1161/01.res.60.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myosin isoenzymes, ATPase activity, and contraction duration in rat cardiac muscle with aging can be modulated by thyroxine.

Abstract: To determine whether the relative decline in cardiac myosin isoenzyme V, with maturation continues progressively into senescence and whether thyroxine could reverse age-associated changes in the myosin isoenzyme profile and contraction, rats 2, 8, and 24 months old were treated with thyroxine, 6.4 mg/kg, for 7 days. Myosin isoenzymes, Ca 2+ -myosin ATPase activities, and isometric contractile function were measured in cardiac preparations from thyroxine-treated animals and age-matched controls. Right ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 60 publications
7
42
0
Order By: Relevance
“…Expression of mRNAs encoding the SR Ca2+-ATPase and cardiac calsequestrin in the rat LV myocardium. RNA blot hybridization was carried out with cDNA clones specific for the rabbit cardiac-slow twitch skeletal SR Ca2+-ATPase (27) and canine cardiac calsequestrin (25). The SR Ca2+-ATPase cDNA probe (pCA) hybridized with an mRNA species of -4 kb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of mRNAs encoding the SR Ca2+-ATPase and cardiac calsequestrin in the rat LV myocardium. RNA blot hybridization was carried out with cDNA clones specific for the rabbit cardiac-slow twitch skeletal SR Ca2+-ATPase (27) and canine cardiac calsequestrin (25). The SR Ca2+-ATPase cDNA probe (pCA) hybridized with an mRNA species of -4 kb.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological studies of LV papillary muscle preparations have revealed that the duration of tension and the time to half-relaxation were prolonged in aged rats compared with in their younger cohort (21, 24). The prolongation of myocardial contraction has been attributed to a decline ofCa2+-activated myosin-ATPase activity, secondary to a decrease in the percentage of a-MHC or V1 isozyme (25,26). The abnormal myocardial relaxation has been thought to reflect age-related decreases in Ca2+-uptake by the SR (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, V3 exhibits a greater economy of force production than V1 [4]. Thus myosin isozyme composition is related to myocardial performance [5,6]. Furthermore, the myosin isozyme composition of ventricular muscle is developmentally, physiologically, and hormonally regulated [7].…”
mentioning
confidence: 99%
“…A number of age-associated biochemical alterations may contribute to the aging changes seen at the cellular level. In rodents, one of the most prominent biochemical changes in the aging myocardium is the shift of the myosin isozyme profile from the fast, V 1 isoform to the slow, V 3 isoform (8,15,25,34,37). This shift is involved in and/or is associated with changes in many of the physiological parameters mentioned above.…”
mentioning
confidence: 99%